Myosin heavy chain-like localizes at cell contact sites during Drosophila myoblast fusion and interacts in vitro with Rolling pebbles 7. - Bonn, B.R.; Rudolf, A.; Hornbruch-Freitag, C.; Daum, G.; Kuckwa, J.; Kastl, L.; Buttgereit, D.; Renkawitz-Pohl, R. (Experimental Cell Research, 2013)
Besides representing the sarcomeric thick filaments, myosins are involved in many cellular transport and motility processes. Myosin heavy chains are grouped into 18 classes. Here we show that in Drosophila, the unconventional group XVIII myosin heavy chain-like (Mhcl) is transcribed in the mesoderm of embryos, most prominently in founder cells (FCs). An ectopically expressed GFP-tagged Mhcl localizes in the growing muscle at cell-cell contacts towards the attached fusion competent myoblast (FCM). We further show that Mhcl interacts in vitro with the essential fusion protein Rolling pebbles 7 (Rols7), which is part of a protein complex established at cell contact sites (Fusion-restricted Myogenic-Adhesive Structure or FuRMAS). Here, branched F-actin is likely needed to widen the fusion pore and to integrate the myoblast into the growing muscle. We show that the localization of Mhcl is dependent on the presence of Rols7, and we postulate that Mhcl acts at the FuRMAS as an actin motor protein. We further show that Mhcl deficient embryos develop a wild-type musculature. We thus propose that Mhcl functions redundantly to other myosin heavy chains in myoblasts. Lastly, we found that the protein is detectable adjacent to the sarcomeric Z-discs, suggesting an additional function in mature muscles.